Successful Interview Skills - Corfield, Rebecca (London : Kogan Page, 2006)
Written for a wide audience, 'Successful Interview Skills' contains invaluable advice and techniques on everything from what to wear to dealing with troublesome situations during job interviews.
Previous ed.: 2002.
Includes bibliographical references (p. 119-121) and index.
Keywords: Employment interviewing; Careers